(3GdeYLe GdChSWs - (3CHh GdbGSe SdjeGf Hf CMeO GjhH Hf eWjQ GddNej GdTGej GdWHQGfj,J (B360 (3g` s
(3ChdgG (B:s
(3jHJOF ef GdLRA (B38 s
(3LRA efg jHJOF ef GdLRA (B38 (3Edi BNQ GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B121s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B106 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1737s
Keywords: (3GdMOjK h GdeUWdMs